Cultural Contexts of Domestic and Juvenile Violence: A Cross-Cultural Perspective from Germany, Turkey and Norway - Uslucan, Haci-Halil (International Journal of Criminology and Sociology, 2013)
The use of violence by parents in child rearing and acts of juvenile violence, which are often intertwined, up to the present day represent serious developmental, cultural and practical challenges, although the rates of domestic violence show a slight decrease in many European countries. This study examines three selected countries, Norway, Germany and Turkey, on the extent to which experiences of domestic violence and harsh parenting are associated with juvenile violence. For this purpose, 386 German, 386 Turkish and 322 Norwegian juveniles (aged 13 to 20 years) were interviewed at schools in Magdeburg, Germany (in the former GDR), Kayseri (Turkey), and Oslo and Tönsberg (Norway) from June 2001 to April 2002, using a standardised questionnaire with 5-point Likert-rating scales. The scales measured maternal violence within the home, family climate, personal and familial risks and variables of juvenile violence (e.g., acceptance of violence, perpetrating violence, and victimisation). The results of this cross-cultural study show significant differences between the three countries examined here regarding both active juvenile violence and the acceptance of violence. Furthermore, both the experience of domestic violence as well as the climate within the family unit points out remarkable differences. Lastly, the results of multiple regression analyses reveals that the proposed model, in which maternal domestic violence, irritability and gender were the predictors of juvenile violence, could explain a great range of variance, especially among German juveniles.